Submucosal Injection of the RNA Oligonucleotide GUT-1 in Active Ulcerative Colitis Patients: A Randomized, Double-Blind, Placebo-Controlled Phase 2a Induction Trial. - Atreya, Raja; Kühbacher, Tanja; Waldner, Maximilian; Hirschmann, Simon; Drvarov, Oliver; Abu Hashem, Raed; Maaser, Christian; Kucharzik, Torsten; Dinter, Johanna; Mertens, Jessica; Schramm, Christoph; Holler, Babett; et al. (Journal of Crohns & Colitis, 2024)
BACKGROUND AND AIMS: Carbohydrate sulfotransferase 15 [CHST15] biosynthesizes sulphated matrix glycosaminoglycans and is implicated in intestinal inflammation and fibrosis. Here, we evaluate the efficacy and safety of the double-stranded RNA oligonucleotide GUT-1, a specific blocker of CHST15, as induction therapy in patients with ulcerative colitis [UC]. METHODS: In this randomized, double-blind, placebo-controlled, phase 2a study, we enrolled endoscopically active UC patients, refractory to conventional therapy, in five hospital centres across Germany. Patients were randomized 1:1:1 using a block randomized technique to receive a single dosing of 25 nM GUT-1, 250 nM GUT-1, or placebo by endoscopic submucosal injections. The primary outcome measure was improvement of endoscopic lesions at weeks 2 or 4. The secondary outcome measures included clinical and histological responses. Safety was assessed in all patients who received treatment. RESULTS: Twenty-eight patients were screened, 24 were randomized, and 21 were evaluated. Endoscopic improvement at weeks 2 or 4 was achieved by 71.4% in the GUT-1 250 nM, 0% in the GUT-1 25 nM, and 28.6% in the placebo group. Clinical remission was shown by 57.1% in the GUT-1 250 nM, 0% in the GUT-1 25 nM, and 14.3% in the placebo groups. Histological improvement was shown by 42.9% in the GUT-1 250 nM, 0% in the GUT-1 25 nM, and 0% in the placebo groups. GUT-1 250 nM reduced CHST15 expression significantly and suppressed mucosal inflammation and fibrosis. GUT-1 application was well tolerated. CONCLUSION: Single dosing by submucosal injection of GUT-1 repressed CHST15 mucosal expression and may represent a novel induction therapy by modulating tissue remodelling in UC.
EVALuna2:550699